The era of genome editing: current updates and the status of food and nutrition security - Fathy Khaled; Sahil Mehta; Pawan Kumar Agrawal; Usama M. Abdel-Monem; Hend El-Akkad; Ahmed S. Gendy; Sherin H. A. Al-Maracy; Rania M. Y. Heakel; Hany A. Wafa; Rania Fathy; Om Prakash Narayan (Frontiers in Sustainability, 2024)
Food security is the situation in which all people around the globe, in all circumstances must maintain constant physical and financial access to adequate nutritious, clean, and safe food. This is why food security is regarded as a major global issue. Domestically and internationally, many factors affect food production and quality; these include environmental climate change conditions, disasters, emerging new diseases, political issues, and shifts in the global economy. Additionally, rapid population growth necessitates adjustments to food and crop production. The current agricultural production strategies negatively affect soil fertility and cause many defects such as desertification, deforestation, and increased soil salinity. Additionally, the high use of chemical fertilizers and pesticides affects human health and food production. The production of numerous strategic crops, including rice, maize, soybeans, and wheat, was reduced due to the aforementioned factors. The global hunger index increased, and millions of people were placed in the food insecurity red zone. Governments and societies attempted to address the problem by creating a new one: a higher yield of low-quality main food crops, which can give rise to hidden hunger, a serious issue that violates people’s rights to a healthy and nutritious diet and inevitably causes food insecurity. In an attempt to end hunger, the Green Revolution produced high-yielding varieties of crops; however, this came at the expense of massive amounts of chemical pesticides, fertilizers, and other agricultural activities and practices that ignored the negative effects on the environment and nutritional value. Yet, billions of people worldwide suffer from iron, zinc, iodine, and vitamin A deficiency, making hidden hunger, malnutrition, and micronutrient deficiencies a severe and widespread nutritional issue in developing nations. The most common nutritional condition affecting poor and rural populations, especially those in low-income developing countries, is iron and zinc deficiency. To decrease and close the gap between crop production and food consumption, there is a need to increase agricultural productivity. Here we discussed the current status of food insecurity and malnutrition status where many research efforts and developments to enhance food quality and production for food crops with the help of genome editing tools and applications for sustainable food production.